Küresel-yerel tartışmaları bağlamında “Recep İvedik” - Tüzün, Selin (My University, 2011)
Global, Local, Consumer Culture, Identity, Recep Ivedik ABSTRACT AN ANALYSIS OF RECEP IVEDIK WITHIN THE CONTEXT OF GLOBAL-LOCAL DEBATE As the production and consumption practices became worldwide, and the mobility of the capital increased, major transformations have occured in economic, cultural and social life. The importance of consumption in everyday life increased. The homogenising effects of global consumer culture increased as well as the quest for particularities. The invasive tendencies of global consumer culture provoked defensive reactions. Thus the local has been defined as the sphere of authentic culture in contrast to the culture of capital. The class gaps widened due to globalization process have become visible in consumption practices and life style patterns, and nourished the cultural conflicts. Having a remarkable box office success and provoking many debates, Recep Ivedik movies are full of clues which help us to understand Turkey in 2000’s. Critising the Westernised “new middle class” life style through humour, the movies use dichotomies like authenticity, fakeness etc., and exalt the “traditional” as the authentic against the Westernised. What is more, being produced in a certain period, under certain production circumstances, the production, marketing and exhibition processes of Recep Ivedik movies help us to understand the transformations of Popular Turkish Cinema through local and global interactions.
Keywords: Komedi Filmleri; Komedyenler